2017
DOI: 10.1113/ep086436
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific differences in cardiovascular and metabolic hormones with integrated signalling in the paraventricular nucleus of the hypothalamus

Abstract: What is the topic of this review? We describe roles of crucial signalling molecules in the paraventricular nucleus of the hypothalamus and highlight recent data suggesting sex-specific changes in the expression of crucial signalling molecules and their receptors, which may underlie sex differences in both cardiovascular and metabolic function. What advances does it highlight? This review highlights the integrative capacity of the paraventricular nucleus in mediating cardiovascular and metabolic effects by inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In rat brain, all SRPX2‐ir neurons were located in the hypothalamus (Figure a), particularly in the Pa, Pe (Figure a 1 ), and SO nuclei (Figure a 2 ). In the Pa, SRPX2‐ir neurons were distributed bilaterally in all functional compartments within the nucleus, including the neurosecretory magnocellular neurons, endocrine, and pre‐autonomic parvocellular neurons (Ferguson, Latchford, & Samson, ; Loewen et al, ; Swanson & Sawchenko, ). The cytoplasmic SRPX2 protein had a granular appearance when observed at a higher magnification (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat brain, all SRPX2‐ir neurons were located in the hypothalamus (Figure a), particularly in the Pa, Pe (Figure a 1 ), and SO nuclei (Figure a 2 ). In the Pa, SRPX2‐ir neurons were distributed bilaterally in all functional compartments within the nucleus, including the neurosecretory magnocellular neurons, endocrine, and pre‐autonomic parvocellular neurons (Ferguson, Latchford, & Samson, ; Loewen et al, ; Swanson & Sawchenko, ). The cytoplasmic SRPX2 protein had a granular appearance when observed at a higher magnification (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the SRPX2‐ir neurons were located in the Pa, which has three functional compartments. These include the neurosecretory magnocellular neurons projecting to the posterior pituitary, the neuroendocrine parvocellular neurons projecting to the median eminence, and the pre‐autonomic parvocellular neurons projecting to the nucleus tractus solitarius, rostral ventrolateral medulla, and spinal cord (Ferguson et al, ; Loewen et al, ; Swanson & Sawchenko, ). This explains the observed topographic organization of SRPX2‐ir projections to the hypophysis and brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…A potential link with CAN could be established considering the effect of adipose hormones on central neuronal activity. Among the adipokines, adiponectin and nesfatin have been found to exert metabolic and cardiovascular regulatory functions within the hypothalamic paraventricular nucleus [ 77 ]. Hence, it would be reasonable to assume that an alteration in the adipokine profile caused by adipose inflammation would have an impact on central neuronal function.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, food and drug seeking behavior engages the orexin system differentially in males and females. Further support for increased orexin function in females comes from a recent study in which OX 2 R expression in the PVN was found to be higher in female rats compared with male rats (Loewen et al, 2017). Increased OX 2 R expression might suggest increased orexin action at the apex of the HPA response; this might explain, in part, how orexins exacerbate the response to stress in female rats.…”
Section: Sex Differences In Orexinsmentioning
confidence: 93%